Role of sensation seeking and aggression on risk riding behaviors among motorcycle street racers in Malaysia - Rozmi Ismail; Normah Che Din; Ong, Lee Lee; Norhayati Ibrahim; Fauzi Sukimi (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2015)
In Malaysia, Illegal motorcycle street racers (locally known as Mat Rempit) is a well known phenomena. Racing on the public roads and performing dangerous stunts action not only endangered themselves but also threaten other road users. This article examines the relationship between impulsive traits, sensation seeking, aggression and risk taking behaviors among illegal motorcycle street racers in Malaysia. Some 564 motorcyclists (identified as Mat Rempit) were interviewed and requested to complete self-reported questionnaires on aggression, sensation seeking, and risky riding. This study found that the Mat Rempit who participated in illegal street racing scored higher on aggression, sensation seeking, and risk taking behaviors as compared to the group of respondents not involved. Results also revealed that those higher on overall impulsive sensation seeking traits also scored relatively high on aggression and risky riding. Regression analysis showed aggression, and sensation seeking behaviors contributed to 16.1% of the total variance in risky riding. This study suggested that effective enforcement as well as special rehabilitation program is needed for this group.